Influence of drying methods to quality of meniran herb (Phyllanthus niruri LINN.) - Rivai, Harrizul; Nurdin, Hazli; Suyani, Hamzar; Bakhtiar, Amri (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2011)
Effects of drying methods in obtaining the extractive, phenolic content and antioxidant activity in Phyllanthus niruri Linn. herbs have been investigated. The drying methods tested were air-drying at ambient temperature, oven-drying at 40 °C, oven-drying at 60 °C, and fresh samples as control. Results revealed that drying of the fresh plant caused the decrease of extractive obtainability, phenolic content and antioxidant activity. There were significant differences among drying methods (p < 0.05). Among the drying methods tested, the best result was by oven-drying at 40 °CKey words: Antioxidant, Phyllanthus niruri Linn., drying methods, phenolic compounds